"Žrtvi sta, ne pa storilca" - Mrak, Anja (Ars et humanitas, 2018)
In her 1997 novel The God of Small Things, Arundhati Roy confronts the problem of caste violence, inextricably bound up with other practices of social domination such as patriarchy, racism, colonialism and neocolonialism, through a complex narrative structure. The conventional story about a tragic love between a woman from a higher caste and a member of the untouchables skilfully evades cliché patterns by employing eccentric focalisers, as we experience most of the story through the lenses of multiple-person narrators, twin brother and sister, Rahel and Estha, magical realism, and a disjointed narrative full of prolepses and analepses which subtly renders traumatic memories. The novel is structured as a prototypical trauma narrative and stages a confrontation with an unresolved traumatic event from which Rahel and Estha have been recovering since childhood. Roy deftly transposes the dualism of caste purity and impurity onto the narrative structure. The narrative is caught within a duality (symbolised already by the twins) and a perpetual repetition which represents not only the eternal return of trauma but also the constant tension which derives from the hegemony of the caste system and the violence it produces. The biopolitics of social mechanisms and structures which disciplines the individual's body, controls his actions, rectifies and sanctions transgressions is at the heart of the novel. It raises the individual into obedience and restraint with the help of state institutions, and regulates them into an inconspicuous collective body in the name of security, unity and higher common goals. Socio-political mechanisms are legitimised and reaffirmed through violence as well, which is not understood as such, but rather as a necessary "measure" and "duty" to uphold the law.
Keywords: Indian literature; indijska književnost; množinski pripovedovalec; multiple-person narrator; narrative structure; nasilje; postcolonial literatures; postkolonialne književnosti; pripovedna struktura; Roy, Arundhati; trauma; travma; violence